VARIASI MORFOLOGIS DAN MOLEKULAR IKAN NILEM (Osteochilus hasselti Cuvier & Valenciennes, 1842) DI SUNGAI SERAYU DAN BALAI BENIH IKAN PANDAK PURWOKERTO - , Anggari Linda D; , Dr. Niken Satuti Nur Handayani, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Silver sharkminnow (Osteochilus hasselti) is one of freshwaterfish species which potential to be developed. Information regarding morphological dan genetic variations are required to support Silver sharkminnow farm. The aims of this study were to know morphological and genetic variation of Silver sharkminnow from Serayu River and Pandak Fish Hatchery Purwokerto. Silver sharkminnow samples were collected using survey method with purposive sampling. Fourty samples of Silver sharkminnow from Serayu River and ten samples from Pandak Fish Hatchery were collected. Fifty three morphological of fifty Silver sharkminnow samples were observed. Fourteen molecular characters of twenty four Silver sharkminnow samples were observed using PCR-ISSR (Polymerase Chain Reaction-Inter Simple Sequence Repeat) method. All collected data analyzed using MVSP 3.22. Dendogram resulted by morphological characters analyzis showed three cluster. The highest similarity percentage value was Serayu-Banjarnegara and Serayu-Banyumas population (95,918%). Dendogram resulted by molecular characters analyzis showed three cluster with the lowest similarity percentage was Pandak Fish Hatchery population. The conclusion of this research is morphological and molecular variation generated 3 cluster of Silver sharkminnow population.